Prostaglandin signalling in cerebral ischaemia - Andreasson, Katrin (Blackwell Publishing Ltd, 2010)
The inducible cyclooxygenase COX-2 exerts neurotoxic effects in a wide spectrum of neurological disease models, including models of cerebral ischaemia and chronic neurodegeneration. As COX-1 and COX-2 catalyse the first committed step in prostaglandin synthesis, recent efforts have focused on identifying the downstream prostaglandin signalling pathways responsible for mediating the toxic effect of COX-2. Recent studies in models of in vitro excitotoxicity or hypoxia demonstrate that certain prostaglandin receptors mediate toxic effects, but a large number appear to mediate paradoxically protective effects. In vivo studies have begun to confirm initial in vitro findings, with selected prostaglandin receptors eliciting either neurotoxic or protective effects in models of cerebral ischaemia. In the present issue, Ikeda-Matsuo et al. examine the function of the PGE(2) EP3 receptor in a model of transient focal ischaemia and explore its potential signalling through Rho kinase activation. This article is a commentary on Ikeda-Matsuo et al., pp. 847–859 of this issue. To view this paper visit http://dx.doi.org/10.1111/j.1476-5381.2010.00711.x